Consumer Acceptability and Sensory Profile of Cooked Broccoli with Mustard Seeds Added to Improve Chemoprotective Properties. Issue 9 (25th August 2014) - Ghawi, Sameer Khalil; Shen, Yuchi; Niranjan, Keshavan; Methven, Lisa
Abstract Broccoli, a rich source of glucosinolates, is a commonly consumed vegetable of the Brassica family. Hydrolysis products of glucosinolates, isothiocyanates, have been associated with health benefits and contribute to the flavor of Brassica. However, boiling broccoli causes the myrosinase enzyme needed for hydrolysis to denature. In order to ensure hydrolysis, broccoli must either be mildly cooked or active sources of myrosinase, such as mustard seed powder, can be added postcooking. In this study, samples of broccoli were prepared in 6 different ways; standard boiling, standard boiling followed by the addition of mustard seeds, sous vide cooking at low temperature (70 °C) and sous vide cooking at higher temperature (100 °C) and sous vide cooking at higher temperature followed by the addition of mustard seeds at 2 different concentrations. The majority of consumers disliked the mildly cooked broccoli samples (70 °C, 12 min, sous vide) which had a hard and stringy texture. The highest mean consumer liking was for standard boiled samples (100 °C, 7 min). Addition of 1% mustard seed powder developed sensory attributes, such as pungency, burning sensation, mustard odor, and flavor. One cluster of consumers (32%) found mustard seeds to be a good complement to cooked broccoli; however, the majority disliked the mustard‐derived sensory attributes. Where the mustard seeds were partially processed, doubling the addition to 2% led to only the same level of mustard and pungent flavors as 1% unprocessed seeds, and mean consumer liking remained unaltered. This suggests that optimization of the addition level of partially processed mustard seeds may be a route to enhance bioactivity of cooked broccoli without compromising consumer acceptability.